ChemInform Abstract: Heterogeneously Catalyzed Direct C—H Thiolation of Heteroarenes. Issue 38 (3rd September 2015) - Vasquez‐Cespedes, Suhelen; Ferry, Angelique; Candish, Lisa; Glorius, Frank
Abstract An operationally simple general methodology for the arylthiolation of heteroarenes including thiophene, benzothiophene, benzofuran, and indole derivatives is elaborated.